Strongly divergent impact of adherence patterns on efficacy of colorectal cancer screening: the need to refine adherence statistics - Heisser, Thomas; Cardoso, Rafael; Guo, Feng; Möllers, Tobias; Hoffmeister, Michael; Brenner, Hermann (Clinical and translational gastroenterology, 2021)
INTRODUCTION: - The performance of colorectal cancer (CRC) screening programs depends on the adherence to screening offers. However, identical adherence levels may result from varying patterns of the population's screening behavior. We quantified the effects of different adherence patterns on the long-term performance of CRC screening for annual fecal immunochemical testing and screening colonoscopy at 10-year intervals. - METHODS: - Using a multistate Markov model, we simulated scenarios where, while at the same overall adherence level, a certain proportion of the population adheres to all screening offers (selective adherence) or the entire population uses the screening offers at some point(s) of time, albeit not in the recommended frequency (sporadic adherence). Key outcomes for comparison were the numbers of prevented CRC cases and prevented CRC deaths after 50 simulated years. - RESULTS: - For screening with annual fecal immunochemical testing at adherence levels of 10%-50%, ratios of prevented CRC cases (CRC deaths) resulting from a sporadic vs a selective pattern ranged from 1.8 to 4.4 (1.9-5.3) for men and from 1.7 to 3.6 (1.8-4.4) for women, i.e., up to 4-5 times more CRC cases and deaths were prevented when the population followed a sporadic instead of a selective adherence pattern. Comparisons of simulated scenarios for screening colonoscopy revealed similar patterns. - DISCUSSION: - Over a lifelong time frame, large numbers of irregular screening attendees go along with much larger preventive effects than small numbers of perfectly adhering individuals. In clinical practice, efforts to reach as many people as possible at least sporadically should be prioritized over efforts to maximize adherence to repeat screening offers.
Gesehen am 01.12.2021